Efeitos da aplicação de selênio exógeno sobre a fisiologia de mudas de eucalipto cultivadas em condições de salinidade - Santos Junior, Ramon Negrão (2023)
Selenium (Se) is not yet considered an essential element for plant metabolism. However, it is well documented that in adequate doses Se can be beneficial to plants and improve stress tolerance mechanisms. In this scenario, the objective of this work was to evaluate the effects of applying Se (0, 1, 5 and 25 μM) in two eucalyptus genotypes (VCC 865 and AEC 0144) cultivated or not in saline conditions (0 and 100 mM NaCl). The experiment was carried out in a completely randomized design and each genotype consisted of an independent experiment. After 60 days of treatment, growth, biomass, concentration of ions (K+ , Na+ and Ca2+) in plant tissues, chlorophyll a fluorescence, gas exchange and pigment content were evaluated. The data obtained were submitted to ANOVA and compared using the Duncan test (p < 0.05). The observed results showed that salinity significantly affected the height, collar diameter (Dc), biomass, net photosynthetic rate (PN), transpiration rate (TR), stomatal conductance (gs), maximal quantum efficiency of PSII (FV/ FM), the concentration of K+ , Na+ and Ca2+ ions in plant tissues. However, the application of Se was able to increase the concentration of K+ in the roots, reduce the concentration of Na+ in the leaves and attenuate the disturbances observed in the L-band and in the other parameters of the JIP test (Area, ABS/RC, RE0/RC, ϕP0, ψE0, ϕE0, δR0, ϕR0, PIABS e PItotal). The same effects were not observed on the K-band. The content of chloroplast pigments was also not influenced by salinity or Se application. Finally, it was concluded that the application of 1 and 5 μM of Se was able to reduce the concentration of Na+ in the leaves, improving cellular homeostasis, the performance of the light-harvesting complex II and energy conservation in the photosynthetic apparatus of VCC 865 and AEC 0144 seedlings.